2014
DOI: 10.1177/2050312114530282
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes following in utero exposure to buprenorphine/naloxone or methadone

Abstract: Objectives:To study neonatal outcomes following buprenorphine/naloxone and methadone exposure during pregnancy.Methods:This study is a retrospective review of clinical and demographic information of 58 infants whose mothers were treated with buprenorphine/naloxone and 92 infants whose mothers were treated with methadone for opioid dependence during pregnancy.Results:Gestational age, birth weight, prematurity, admission to neonatal intensive care unit, and length of stay were similar between both groups of infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The NICU admission rates of neonates exposed to other forms of MAT ranged from 20% to 39%, which, on a study-bystudy basis, were not significantly different. 20,21,23 Four study groups compared the need for treatment of neonatal abstinence syndrome after maternal treatment with buprenorphine-naloxone vs other forms of MAT. Of the buprenorphinenaloxoneeexposed neonates, the need for NAS treatment ranged from 25% to 64%, whereas neonates exposed to other forms of MAT ranged from 51% to 80%.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The NICU admission rates of neonates exposed to other forms of MAT ranged from 20% to 39%, which, on a study-bystudy basis, were not significantly different. 20,21,23 Four study groups compared the need for treatment of neonatal abstinence syndrome after maternal treatment with buprenorphine-naloxone vs other forms of MAT. Of the buprenorphinenaloxoneeexposed neonates, the need for NAS treatment ranged from 25% to 64%, whereas neonates exposed to other forms of MAT ranged from 51% to 80%.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Of the buprenorphinenaloxoneeexposed neonates, the need for NAS treatment ranged from 25% to 64%, whereas neonates exposed to other forms of MAT ranged from 51% to 80%. 20,21,23, 24 Gawronski et al 21 and Wiegand et al 20 reported a significantly decreased need for NAS treatment when buprenorphine-naloxoneeexposed neonates were compared with those exposed to methadone. Mullins et al 23 reported that significantly fewer buprenorphine-naloxoneeexposed neonates required treatment for NAS than those exposed to buprenorphine alone; however, this finding did not persist after adjustment for confounders.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational cohort studies reviewing neonatal outcomes when their mothers were treated with buprenorphine/naloxone demonstrated outcomes similar to those whose mothers were treated with methadone or buprenorphine monotherapy. [6][7][8][9] Citing lack of safety data, most authorities recommend that pregnant women who are treated with buprenorphine/ naloxone at conception switch to either buprenorphine monotherapy or methadone. 3,19,20 Safety concerns may include fetal or neonatal withdrawal from the presence of naloxone in combination with opioids; adult studies show that if naloxone is given sublingually it does not affect the efficacy or pharmacological properties of buprenorphine.…”
Section: Commentmentioning
confidence: 99%
“…5 Advantages for utilizing buprenorphine compared with methadone include its office-based prescribing ability (vs. daily distribution of methadone), lower drug interaction profile, lower overdose potential, and less severe NAS. 5 There is emerging information on the treatment of pregnant women utilizing the MAT combination medication buprenorphine/naloxone, [6][7][8][9] which is widely used in the addiction medicine treatment community for nonpregnant individuals.…”
mentioning
confidence: 99%